Effects of volatilities on property sector indices of ASEAN-6 pre, during, and after the Global Financial Crisis and during the COVID-19 pandemic from 2006 to 2022 - Acuña, Maria Charizza (Animo Repository, 2022)
This paper analyzed the effects of volatilities, specifically in terms of their magnitude and direction on ASEAN-6 property market index returns spanning from the Global Financial Crisis until the COVID-19 pandemic from 2006 to 2022. The study also tackled whether COVID-19 waves had a significant impact on the said returns. The empirical investigation was conducted using daily closing property market index returns and daily COVID cases in Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. Three statistical tests examined the different effects of volatilities, namely Johansen’s Cointegration test, the Granger Causality test, and the GJR-GARCHX test. Findings revealed that the general COVID-19 pandemic and its waves are cointegrated with the ASEAN-6 property market index returns and are not the attributable cause of fluctuations in the volatilities. Only three countries, namely, Indonesia, Malaysia, and the Philippines, were significantly impacted by the pandemic. Volatility clustering, which was actualized during the pandemic, significantly impacted the property market indices for these three countries. There is no sufficient evidence to support that the individual waves of COVID were significant enough to affect all ASEAN countries under study, excluding Vietnam. The property market indices of Singapore and Thailand exhibited resilience based on their low volatility dispersion during the pandemic compared to the erratic and wide volatility dispersion during the GFC. This study would help investors prepare portfolio strategies to mitigate the high volatility clustering during a pandemic crisis and assist financial regulators in policy formulation to revive their economies during a pandemic crisis within ASEAN-6 countries.